(3QSGdI aj GdYed HQHY GdOGFQI GdehVhY Ydjg GdebfWQGJ GdeWhjIs - (3YHO Gddg Hf Ndjd Hf jhSa, LeGd GdOjf GdeGQOGfj,J (B809 (3g` s
(3ChdgG (B:s
(3HYO GdHSedI hGdMeOdg č agPg fHPg ai GdYed HQHY GdOGFQI GdehVhY Ydjg GdebfWQGJ GdeWhjI s
(3BNQgG (B:s
(3Ef gPg GdBdg jYed HgG LejY eG jYed HGdebfWQGJ GdTeGdjI hGdLfhHjI hjYed ajgG HLejY GdchGcH s
(3Vef eLehY , JQJjHgG (B: (3ef U (B3 - (3U(B5s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B85 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B53s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B169 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B46 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3ejbGJ (B138) s
Keywords: (3Gdadcs